ANALISIS PROBLEM MANAGEMENT PADA IT HELPDESK UIN RADEN FATAH DENGAN IMPLEMENTASI ITSM: STUDI KASUS PELAYANAN DARI UNIT PUSTIPD (PUSAT TEKNOLOGI INFORMASI DAN PANGKALAN DATA) - M Aswadi; Tata Sutabri; Zena Lusi (Pusat Riset dan Inovasi Nasional, 2024)
Problem Management is a crucial aspect in the management of Information Technology (IT) services, aiming to identify and address the main causes of problems in an organization's IT infrastructure. This study analyzes the implementation of Problem Management in the IT Helpdesk at UIN Raden Fatah, with a focus on services from the PUSTIPD Unit. Case studies are used as the main research method, involving interviews, observation and analysis of related documents. The findings show that the implementation of Problem Management has brought significant benefits, although there is still room for improvement, especially in interunit coordination and end-user engagement. This study provides insight into the importance of Problem Management in improving the performance of IT services in higher education institutions.